2016
DOI: 10.1038/srep23097
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Attenuates Adipose Tissue Inflammation in vitro and Adipose Tissue Fibrosis through Inhibition of Innate Immune Responses in Mice

Abstract: Isoliquiritigenin (ILG) is a flavonoid derived from Glycyrrhiza uralensis and potently suppresses NLRP3 inflammasome activation resulting in the improvement of diet-induced adipose tissue inflammation. However, whether ILG affects other pathways besides the inflammasome in adipose tissue inflammation is unknown. We here show that ILG suppresses adipose tissue inflammation by affecting the paracrine loop containing saturated fatty acids and TNF-α by using a co-culture composed of adipocytes and macrophages. ILG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 53 publications
1
54
0
Order By: Relevance
“…Mincle has previously been described as a proinflammatory marker of M1 polarization stimulated by TLR-4/nuclear factor- (NF-) κ B signalling, which is the main pathway involved in ATM activation [32, 33]. Another gene that may play a regulatory role during adipose tissue resident macrophage differentiation is Tribbles homolog 1 (Trib1).…”
Section: Adipose Tissue Inflammationmentioning
confidence: 99%
“…Mincle has previously been described as a proinflammatory marker of M1 polarization stimulated by TLR-4/nuclear factor- (NF-) κ B signalling, which is the main pathway involved in ATM activation [32, 33]. Another gene that may play a regulatory role during adipose tissue resident macrophage differentiation is Tribbles homolog 1 (Trib1).…”
Section: Adipose Tissue Inflammationmentioning
confidence: 99%
“…Histological analysis revealed that HFD treatment induced extensive interstitial fibrosis in eWAT, which was markedly suppressed by ILG supplementation (0.5% w/w in HFD) [51]. HFD treatment increased collagen 1, TGF-β, TIMP-1, and PDGF-B mRNA expression in eWAT.…”
Section: Inhibitory Effects Of Isoliquiritigenin On Prr-mediated Adipmentioning
confidence: 95%
“…On the other hand, ILG also acts on adipocytes, and consequently suppresses inflammatory changes elicited by macrophage-derived mediators such as TNF-α [51], suggesting that ILG targets multiple cells that constitute adipose tissue. Moreover, activation of various innate immune sensors is affected by ILG stimulation, consequently suppressing adipose tissue inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISL potently inhibits the activation of the NLRP3 inflammasome and improves diet-induced adipose tissue inflammation [12]. ISL decreases phosphorylated c-Jun N-terminal kinase (JNK) expression in macrophages induced by palmitic acid, and suppresses the induced inflammatory changes by inhibiting nuclear factor kappa B (NFκB) activation [13]. Wu et al demonstrated that ISL inhibits interferon γ induced inflammation in hepatocytes by influencing the activation of JAK1/STAT1, IRF3/MyD88, ERK/MAPK, JNK/MAPK, and PI3K/Akt signaling pathways [14].…”
Section: Introductionmentioning
confidence: 99%